Marx”™s dialectical-empirical method of explanation - Brien, Kevin (Utopía y Praxis Latinoamericana, 1970)
This paper explores Marx”™s mature method of dialectical explanation. Drawing from Marx”™s formulations, the paper proceeds to philosophically elaborate what this method involves. It discloses that: a) all explanatory factors come from prior empirical inquiry; b) this method moves in stages from more abstract levels to more and more concrete levels of explanation; c) the laws figuring in Marx”™s explanations must be interpreted as dialectical tendencies; d) this method is a sort of dialectical synthesis of the “covering law” and “genetic” models of explanation; and e) that it employs the concrete universal and internal relations as fundamental canons of interpretation.